Prospective memory and intraindividual variability in ongoing task response times in an adult lifespan sample: the role of cue focality. Issue 3 (16th March 2017) - Ihle, Andreas; Ghisletta, Paolo; Kliegel, Matthias
ABSTRACT: To contribute to the ongoing conceptual debate of what traditional mean-level ongoing task (OT) costs tell us about the attentional processes underlying prospective memory (PM), we investigated costs to intraindividual variability (IIV) in OT response times as a potentially sensitive indicator of attentional processes. Particularly, we tested whether IIV in OT responses may reflect controlled employment of attentional processes versus lapses of controlled attention, whether these processes differ across adulthood, and whether it is moderated by cue focality. We assessed 150 individuals (19–82 years) in a focal and a nonfocal PM condition. In addition, external measures of inhibition and working memory were assessed. In line with the predictions of the lapses-of-attention/inefficient-executive-control account, our data support the view that costs to IIV in OT trials of PM tasks reflect fluctuations in the efficiency of executive functioning, which was related to failures in prospective remembering, particularly in nonfocal PM tasks, potentially due to their increased executive demands. The additional value of considering costs to IIV over and beyond traditional mean-level OT costs in PM research is discussed.